Catherine the great ebook Portrait of a woman. - Massie, Robert K. (2011)
“[A] tale of power, perseverance and passion . . . a great story in the hands of a master storyteller.”— The Wall Street Journal The Pulitzer Prize–winning author of Peter the Great, Nicholas and Alexandra, and The Romanovs returns with another masterpiece of narrative biography, the extraordinary story of an obscure German princess who became one of the most remarkable, powerful, and captivating women in history. Born into a minor noble family, Catherine transformed herself into empress of Russia by sheer determination. For thirty-four years, the government, foreign policy, cultural development, and welfare of the Russian people were in her hands. She dealt with domestic rebellion, foreign wars, and the tidal wave of political change and violence churned up by the French Revolution. Catherine’s family, friends, ministers, generals, lovers, and enemies—all are here, vividly brought to life. History offers few stories richer than that of Catherine the Great. In this book, an eternally fascinating woman is returned to life.   “[A] compelling portrait not just of a Russian titan, but also of a flesh-and-blood woman.”— Newsweek “An absorbing, satisfying biography.”— Los Angeles Times   “Juicy and suspenseful.”— The New York Times Book Review “A great life, indeed, and irresistibly told.”—Salon NAMED ONE OF THE BEST BOOKS OF THE YEAR BY The New York Times • The Washington Post • USA Today • The Boston Globe • San Francisco Chronicle • Chicago Tribune • Newsweek/ The Daily Beast • Salon • Vogue • St. Louis Post-Dispatch • The Providence Journal • Washington Examiner • South Florida Sun-Sentinel • BookPage • Bookreporter • Publishers Weekly BONUS: This edition contains a Catherine the Great reader's guide.